Tanggung Jawab Rumah Sakit terhadap Pemenuhan Hak Pasien pada Masa Pandemi COVID-19 - Dwi Ratna Kartikawati (Indonesia Law Reform Journal, 2021)
Hospitals are one of the facilities that support efforts in handling Covid-19. Hospitals provide the basis for medical services. The implementer of medical services has many actors in it, so the hospital as part of the facility needs to be legally clarified. Indonesia has issued regulations contained in Law Number 44 of 2009 concerning Hospitals. This study aims to see how the provisions of the legislation in Indonesia accommodate the position of hospitals in handling Covid-19. The analytical method used is qualitative analysis that uses a literature study approach in seeing the development of the number of legal sources. With this method, a number of specific descriptions are obtained that can provide information on how the duties, functions, obligations, and quality standards are supported by legislation for hospitals to be able to optimize medical services. The results of this study indicate that during the Covid-19 pandemic, hospitals have a great responsibility in improving services for patients infected with Covid-19. Various laws and regulations have explained how the central position of hospitals that need to improve medical services during the Covid-19 pandemic is still happening. Good medical services and in accordance with the rules will be a good foundation for handling the Covid-19 pandemic. Keywords: Hospital; Medical Services; Law: Covid-19 Abstrak Rumah sakit menjadi salah satu dari fasilitas yang mendukung upaya dalam penanganan Covid-19. Rumah sakit memberikan dasar untuk pelayanan medis. Pelaksana dari pelayanan medis memiliki banyak aktor didalamnya, sehingga rumah sakit sebagai bagian dari fasilitas perlu diperjelas kedudukan secara hukum. Indonesia telah mengeluarkan peraturan yang tertuang dalam  Undang-Undang Nomor 44 Tahun 2009 Tentang Rumah Sakit. Penelitian ini bertujuan untuk melihat bagaimana kapasitas peraturan perundang-undangan di Indonesia mengakomodir posisi rumah sakit pada penanganan Covid-19. Metode analisis yang digunakan adalah analisis kualitatif yang menggunakan pendekatan studi pustaka dalam melihat perkembangan sejumlah sumber hukum. Dengan metode ini maka didapatkan sejumlah deskripsi khusus yang dapat memberikan informasi mengenai bagaimana tugas, fungsi, hak, kewajiban dan standar mutu yang didukung peraturan perundang-undangan bagi rumah sakit untuk mampu mengoptimalkan pelayanan medis. Hasil penelitian ini menunjukan bahwa pada masa pandemic Covid-19 rumah sakit memiliki tanggung jawab yang besar dalam meningkatkan pelayanan untuk pasien yang terinfeksi Covid-19. Dalam berbagai peraturan perundang-undangan telah dijelaskan bagaimana posisi sentral rumah sakit yang perlu untuk meningkatkan pelayanan medis selama pandemi Covid-19 masih terjadi. Pelayanan medis yang baik dan sesuai dengan aturan akan menjadi landasan baik bagi penanganan pandemi Covid-19.